‘Inclusive’ health systems increase healthy life expectancy - Kostas Athanasakis (James Cook University, 2022)
Introduction: This article attempts to investigate whether inclusive health systems increase societal welfare, with the latter expressed through estimates of healthy life expectancy (HLE). Methods: The analysis uses publicly available data by the Organisation for Economic Co-operation and Development and explores the relationship of HLE at the age of 65 years (HLE_65) with four variables that are representative of institutional inclusivity or extractiveness of health systems. Results: Results indicate that HLE_65 is positively associated with healthcare system institutional inclusivity as expressed in terms of the share of public healthcare expenditure and the spending on preventive care. HLE_65 is inversely associated with the strength of extracting characteristics of the system, such as the market power of physicians and the share of specialists in the total number of physicians. Conclusion: In this light, the development of health policies that aim to strengthen inclusive institutions, such as the focus on prevention, financial protection and primary care, could have a significant positive impact in collective welfare and social cohesion - especially for populations in rural, remote and less developed parts of the world.